Influence of Polymer Seed Coating along with Fungicide, Insecticide and Hoagland Solution in Soybean (Glycine max L.) - TN TIWARI; TK SRIVASTAVA; A B MANDAL; S RAJENDRA PRASAD (Seed Research, 2026)
Pot experiments were conducted during three consecutive years at the research farm of Indian Institute of Seed Science, Mau soybean variety JS-71-05 was taken with three replications under complete randomized design, to study the influence of seed coating with polymers @ 3ml/kg seed, along with different combinations of Blitox (@2.5g/kg seed), Hoagland solution (@5ml/kg seed) and imidachloprid (@2.5ml/kg seed). Results obtained revealed that seed coating with polymers along with combination of blitox, Hoagland solution and imidachloprid in prescribed doses significantly enhanced the seed quality parameters, growth and yield of soybean, over uncoated control as well as overseed coated with polymer alone (@3ml/kg seed. The extent of enhancements in aforesaid characters varied with different combinations and was further increased with increasing number of components in the combinations (T2-Tg); the highest values were noted in T, followed byT5, T, and T6. The treatments applied did not improve the storability of seed in subsequent generation. Conclusively, polymer seed coating in combination withfungicide (Blitox@2.5g/ kg seed), Hoagland solution (5ml/kgseed) and insecticide (imidachloprid @2.5ml/kg seed) may be recommended for improving the seed quality parameters, growth and yield of soybean crop especially when the crop is grown using one year old seed lot.